Characteristics of Internet Addiction Tendency in Sleeping Status and Lifestyle Behaviors among Junior and High School Students using Decision Tree Analysis - Shikano, Akiko; Imai, Natsuko; Noi, Shingo; Katsuzaki, Yumi (Japanese Journal of Health Education for Children, 2023)
The measure against the excessive use of the Internet by children is the urgent issue in the worldwide. On that occasion, it has been pointed out that the necessity to provide children with opportunities to become aware of their own situation. Therefore, this study aimed to clarify the characteristics of Internet dependence tendencies expressed in the sleeping conditions and lifestyle behaviors of junior and high school students as the first work of creating materials to help children recognize their own Internet dependence tendencies. The subjects were children enrolled in four private junior high schools and for private high schools in Kanagawa Prefecture, and data from 3,649 students (valid response rate: 99.5%) with no missing responses were used in the analysis. The survey period was from May to July 2020, during the period of self-restraint to prevent new coronavirus infection and during staggered/dispersed school attendance. In this study, we obtained responses regarding Internet addiction tendency, sleep status, and daily life behavior using Google Form-based unregistered web survey (6 schools) or unregistered questionnaire survey (2 schools). As a result, it was confirmed that the proportion of Internet addiction in the subjects was less pathological internet use, but the addiction tendency including excessive internet use was not much different from the results of the previous study. In addition, in the examination of the relationship between sleep status/living behavior and Internet addiction tendency by decision tree analysis, sleeping status such as “struggling to wake up in the morning” and “getting sleepy during the day” were confirmed. Similarly, behavior associated with smartphone such as “checking one’s smartphone immediately after waking up”, “bringing smartphone to the toilet” and “bringing smartphone to the bed” were confirmed. Not only that, behavior not associated with smartphone use, such as “struggling to remember simple Chinese characters,” “forgetting a lot of things,” and “talking to one’s self” were also confirmed. In the future, the challenges are to improve the accuracy of the materials to help children recognize their own Internet dependence tendencies and to verify this material practically.